Comparison of routine laboratory tests in acute appendicitis and intussusception in childhood (Annals of Medical Research, 2021)
None
Keywords: Childhood; Acute Appendicitis; Idiopathic Intussusception; Laboratory Findings; Clinical Findings; Radiological Finding